PGE2 Is Crucial for the Generation of FAST Whole- Tumor-Antigens Loaded Dendritic Cells Suitable for Immunotherapy in Glioblastoma - Sara Nava; Daniela Lisini; Simona Frigerio; Simona Pogliani; Serena Pellegatta; Laura Gatti; Gaetano Finocchiaro; Anna Bersano; Eugenio Agostino Parati (Pharmaceutics, 2020)
Dendritic cells (DC) are the most potent antigen-presenting cells, strongly inducers of T cell-mediated immune responses and, as such, broadly used as vaccine adjuvant in experimental clinical settings. DC are widely generated from human monocytes following in vitro protocols which require 5−7 days of differentiation with GM-CSF and IL-4 followed by 2−3 days of activation/maturation. In attempts to shorten the vaccine’s production, Fast-DC protocols have been developed. Here we reported a Fast-DC method in compliance with good manufacturing practices for the production of autologous mature dendritic cells loaded with antigens derived from whole tumor lysate, suitable for the immunotherapy in glioblastoma patients. The feasibility of generating Fast-DC pulsed with whole tumor lysate was assessed using a series of small-scale cultures performed in parallel with clinical grade large scale standard method preparations. Our results demonstrate that this Fast protocol is effective only in the presence of PGE2 in the maturation cocktail to guarantee that Fast-DC cells exhibit a mature phenotype and fulfill all requirements for in vivo use in immunotherapy approaches. Fast-DC generated following this protocol were equally potent to standard DC in inducing Ag-specific T cell proliferation in vitro. Generation of Fast-DC not only reduces labor, cost, and time required for in vitro clinical grade DC development, but can also minimizes inter-preparations variability and the risk of contamination.